Material characteristics and failure prediction of SA 213 Superheater Boiler tube in power plant with 315 MW capacity - Nugraha, Ariyana Dwiputra; Harianto, Harianto; Suprihanto, Agus; Sulardjaka, Sulardjaka (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
This study was conducted at the Rembang Semarang Unit 2 power plant in Indonesia, with a capacity of 315 MW. The plant has been in operation since 2011, totaling about 13 years or over 100,000 equivalent operating hours (EOH). High-temperature operations can damage tube materials due to temperature, corrosive environment, pressure, and stress. At the end of 2022, a condenser leak at the plant necessitated an assessment of the boiler tube material. This study focuses on evaluating the SA 213 T91 (chromium (Cr) and molybdenum (Mo) alloy steel) superheater tube, a known for its excellent high-temperature mechanical and thermal properties and corrosion resistance. The research aims to assess potential failures in the boiler tube and guide future operational and maintenance plans. The analysis includes destructive testing, SEM, EDX metallography, and creep rupture testing. Results show corrosion and hard scale deposition inside the tube. Its is shown that creep strength decreases significantly at high temperatures, leading to faster material rupture.